Delving into Chit-Chat with GPT-3.5: Holy Grail or Pandora’s Box? : A Review of AI Opportunities and Challenges in Academia - Griszbacher, Norbert (GILE Journal of Skills Development, 2024)
Historically, technological advancements have continuously transformed our lives in diverse ways. Recently, a sophisticated artificial intelligence (AI) based chatbot called ChatGPT has made similar breakthroughs, revolutionizing various industries and our everyday existence. Education is among the most significantly impacted areas, as ChatGPT opened new doors for both students and teachers. However, as a new phenomenon, it came with challenges within an unexplored grey area, introducing certain threats that persist even after more than a year into the ChatGPT journey. This systematic literature review seeks to analyse the available information concerning the opportunities and threats associated with the use of ChatGPT in academia, aiming to provide a comprehensive overview of the topic. The research suggests that the current version of ChatGPT can be beneficial for students, teachers, and researchers as a digital assistant capable of enhancing productivity through the automation of monotonous and repetitive tasks, provided that its limitations are effectively addressed. Ultimately, the paper provides valuable insights for future discussions, addressing important practical and theoretical considerations. As a conclusion, it is emphasized that while the current use of AI in academic domains presents both opportunities and challenges, the future inevitably involves this technology. Academic and business stakeholders must collaborate proactively worldwide to successfully break down the present myths surrounding ChatGPT, bidding farewell to outdated traditions and implementing essential new policies to guide proper human-AI collaboration.